Testing oral proficiency: what does pronunciation tell us? - Almeida, Vanessa Borges; Consolo, Douglas Altamiro [UNESP] (Universidade Federal de Santa Catarina (UFSC), 2011)
In this study we discuss the role of pronunciation in language testing and investigate two features of pronunciation of eight candidates of the Test of Oral Proficiency in English (TEPOLI) along four bands of the test scale. Deviations in vowel segments and in syllable structure are analyzed. The results point to the need for a global assessment of the candidates’ phonological systems

Neste estudo discute-se o papel da pronúncia na avaliação de proficiência e investigam-se duas características da pronúncia de candidatos no Teste de Proficiência Oral em Língua Inglesa (TEPOLI) ao longo de quatro faixas da escala do teste. São analisados os desvios produzidos em segmentos vocálicos e em estruturas silábicas. Os resultados apontam para a necessidade de uma avaliação global do sistema fonológico dos candidatos
Keywords: language testing; pronunciation; phonology